Promoting an interdisciplinary food literacy framework to cultivate critical citizenship. Issue 4 (8th June 2021) - Rowat, Amy C.; Soh, Michael; Malan, Hannah; Jensen, Leeane; Schmidt, Laura; Slusser, Wendelin
Abstract: The goal of this viewpoint is to promote an integrated and holistic framework for food literacy on college campuses. We propose that a framework to promote an effective understanding of food should encompass social, political, scientific, and personal dimensions; integrating these elements into university curricula and campus culture can empower students to become more engaged food citizens, with implications for their own food choices, and also for the broader food system. Emerging findings show that curricular interventions designed to educate about food system-environment connections can motivate students to reduce red meat and increase vegetable consumption. This viewpoint also lays the foundation for future studies to quantify the impact of increased knowledge on food choices, which can ultimately impact the health and wellbeing of both people and the planet.